Persistensi dan Konsistensi Kinerja Reksadana di Indonesia - Desiyanti, Rika (Jurnal Kajian Manajemen Bisnis, 2014)
Invesment Activity of mutual fund is fund gathering from all investor and managed by invesment manager with forming portofolio. This research test related between past performance with the future performance of mutual fund with the test persistence. This research also test what there is consistency model at measurement of performance of mutual fund in Indonesia. There are three model used in measuring performance of mutual fund, that is Index Sharpe, index Treynor and index Jensen. Sampel in this research is all of share fund. Mutual of share Fund selected because having compared to higher level return three other type mutual fund. Result of research shown in the Indonesia there are abnormal return at mutual fund. This indicate that the invesment manager earn to predict of movement of price sekuritas so that can obtain abnormal return. There is related between past performance with the future performance. This matter explain that historical performance of mutual fund become the especial consideration of investor in chosening mutual fund. There are not consistency among index Sharpe, index Treynor and index Jensen in measuring performance of mutual fund in Indonesia